Generational inequalities and welfare regimes - Louis Chauvel; Martin Schröder (Luxembourg Income Study (LIS), 2014)
This paper uses a new age period cohort model to show that among cohorts born between 1935 and 1975, cohorts born around 1950 are significantly above the income trend in most countries. However, such inequalities between generations are much stronger in conservative, continental European welfare states, compared to social democratic and liberal welfare states. As we show, this is because conservative welfare states expose some cohorts to high youth unemployment and make lifetime earnings dependent on a favorable entry into the labor market. We thus demonstrate that conservative welfare states have put the burden of adjustment to the post-1975 economic slowdown on birth cohorts that could not get stable jobs before 1975, while similar cohort inequalities are much weaker in liberal and social democratic welfare states. In these latter two welfare regimes, the burden of adjustment to the post-1975 economic slowdown was not put on the shoulders of some cohorts relative to others. Our analysis is the first to show which welfare regimes are more conducive to such inequalities between cohorts and what mechanisms lead to these material cohort inequalities.
Keywords: 330